2019
DOI: 10.21608/sjas.2019.52818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipidium sativum seeds extract (Garden cress) on the kidney in sodium nitrite receiving rats

Abstract: This study was carried out to investigate the modulating effect of Lipidium sativum (LS) seeds aqueous extract consumption against sodium nitrite (SN) that induced the nephrotoxicity in male rats. Rats were divided into four groups. Group 1 (control): without any treatment; group 2: injected with a single dose of SN (50 mg/kg body weight) 24 h prior to decapitation intraperitoneally (i.p.); group 3: given orally 300 mg/kg body weight of LS for four weeks; group 4: treated orally with LS for four weeks, then in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In agreement with this finding, Al Hamedan 42 demonstrated that GC seeds suppressed urea and creatinine levels, reducing the risk of acute kidney failure in rats 9 , 10 . This improvement in renal function was due to the active compounds in GC seeds, such as flavonoids and steroidal compounds, as demonstrated in this study, which increase glomerular filtration rate 43 . Moreover, GC seed also has nephroprotective and curative activities 42 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In agreement with this finding, Al Hamedan 42 demonstrated that GC seeds suppressed urea and creatinine levels, reducing the risk of acute kidney failure in rats 9 , 10 . This improvement in renal function was due to the active compounds in GC seeds, such as flavonoids and steroidal compounds, as demonstrated in this study, which increase glomerular filtration rate 43 . Moreover, GC seed also has nephroprotective and curative activities 42 .…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, GC seed also has nephroprotective and curative activities 42 . A previous study reported the ability of GC seeds' aqueous extract to improve the kidneys and restore electrolyte balance and renal functions in sodium nitrite-treated rats 43 . However, flavonoids and phenolic compounds of GC could protect against diabetic nephropathy in streptozotocin-induced diabetic rats, which improved blood urea nitrogen, creatinine, and urine extraction and kidney tissue damage, with a reduction in mitochondrial damage 44 .…”
Section: Discussionmentioning
confidence: 99%
“…They were kept in cages filled with aspen shavings which was changed once to twice a week. The treatment started after one week for twenty-one days, first group fed a standard diet with wheat, second group replaced all wheat with barley, third group fed an equal amount of wheat and barley, fourth and fifth group study the effect of adding 5% Cress seeds with either wheat/ barley with the standard ratio as shown in table (1).…”
Section: Methodsmentioning
confidence: 99%